2016
DOI: 10.1002/mdc3.12437
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Definition of Camptocormia in Parkinson's Disease

Abstract: Background Clinical key aspects of camptocormia in patients with idiopathic Parkinson's disease (PD) await further definition. Methods Based on a self‐assessment of PD patients, we performed an observational study, asking patients with subjectively felt involuntary forward bending to return a questionnaire and provide photographs showing their axial disorder. Forty‐two matched PD patients without subjective signs of camptocormia were recruited as controls. Results The stooped posture of patients with advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 23 publications
3
43
0
1
Order By: Relevance
“…Our results are in line with the findings reported by Margraf and collaborators [26]. In fact, 90% of their camptocormia patients needed walking aids and 93% reported specific disabilities attributed to camptocormia [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with the findings reported by Margraf and collaborators [26]. In fact, 90% of their camptocormia patients needed walking aids and 93% reported specific disabilities attributed to camptocormia [26].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with the findings reported by Margraf and collaborators [26]. In fact, 90% of their camptocormia patients needed walking aids and 93% reported specific disabilities attributed to camptocormia [26]. Since patients with bending angles greater than 30° were more severely affected in ADLs, the authors identified this angle as their diagnostic cut-off [26].…”
Section: Discussionsupporting
confidence: 91%
“…With regard to limitations in ADLs and perceived pain, a study uncorrected for possible confounders involving 145 subjects with PD and FTB did not yield convincing evidence for a threshold angle defining CC (27). Indeed, while showing a significant association between FTB ≥30 • and limitations in ADLs and back pain, the authors remarked that less severe forward angles do not exclude CC (27). They found greater limitations in ADLs in patients with FTB ≥30 • , which is in line with our univariate regression models reported for upper FTB.…”
Section: Discussionmentioning
confidence: 92%
“…Our data are consistent with previous studies indicating that the association between postural abnormalities and such variables may be more closely related to the severity of the PD phenotype and disease progression than to the severity of trunk flexion itself (1, 5). With regard to limitations in ADLs and perceived pain, a study uncorrected for possible confounders involving 145 subjects with PD and FTB did not yield convincing evidence for a threshold angle defining CC (27). Indeed, while showing a significant association between FTB ≥30 • and limitations in ADLs and back pain, the authors remarked that less severe forward angles do not exclude CC (27).…”
Section: Discussionmentioning
confidence: 94%
“…10 En algunos casos, es indoloro, aunque en la mayoría, se asocia con dolor lumbar axial, sobre todo cuando se asocia con la enfermedad de Parkinson. [11][12][13] El SEI difícilmente se confunde con el "síndrome de la cabeza caída" (dropped head syndrome), aunque ambos cuadros comparten muchas de las causas que los originan, se presentan juntos en muy raras ocasiones. 14 Se estima que la edad media de presentación clínica del SEI es de 65 años, el 69% de los pacientes tiene antecedentes de enfermedad de Parkinson y el 25%, de distonía.…”
Section: Discusión Presentación Clínicaunclassified